2020
DOI: 10.1177/0009922820941237
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Health Care Provider Perspectives on Injury Prevention Counseling in Acute and Primary Care Settings

Abstract: The objective of this study was to characterize how pediatric primary care and emergency medicine health care providers and trainees engage in injury prevention counseling and assess perceptions toward injury prevention resources. We surveyed physicians, advanced practice providers, and trainees in the Emergency Department, Primary Care Network, and Pediatric Residency Program at Children’s Hospital of Philadelphia from September to November 2019. Of the 578 eligible participants, 208 (36.0%) completed the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The World Health Organization (WHO) declared this an “infodemic” ( 11 ). It is a task of pediatricians to convey health-related information to parents in an understandable way, enabling them to act accordingly ( 12 , 13 ). Thus, pediatricians had to stay up to date on the latest scientific evidence in order to be able to provide comprehensive care for their patients.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) declared this an “infodemic” ( 11 ). It is a task of pediatricians to convey health-related information to parents in an understandable way, enabling them to act accordingly ( 12 , 13 ). Thus, pediatricians had to stay up to date on the latest scientific evidence in order to be able to provide comprehensive care for their patients.…”
Section: Introductionmentioning
confidence: 99%
“…Health and behavioral service providers may be uniquely poised to provide resources or counsel and assist families as they make transportation-related decisions. Several studies have reported parents, adolescents, and providers themselves consider the teen's primary care physician a resource for information about transportation topics, and in particular, independent driving (Ford et al, 2016;Gaw et al, 2020;Mirman, Goodman, Friedrich, & Ford, 2018). However, a recent survey found only 62% of primary care physicians were comfortable counseling their patients on driving (Gaw et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported parents, adolescents, and providers themselves consider the teen's primary care physician a resource for information about transportation topics, and in particular, independent driving (Ford et al, 2016;Gaw et al, 2020;Mirman, Goodman, Friedrich, & Ford, 2018). However, a recent survey found only 62% of primary care physicians were comfortable counseling their patients on driving (Gaw et al, 2020). Further, autistic individuals may experience unique challenges during provider-patient interactions (e.g., communication and sensory di culties; Duker, Kim, Pomponio, Mosqueda, & Pfeiffer, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Health and behavioral service providers may be uniquely poised to provide resources or counsel and assist families as they make transportation-related decisions. Several studies have reported parents, adolescents, and providers themselves consider the teen's primary care physician a resource for information about transportation topics, and in particular, independent driving (Ford et al, 2016;Gaw et al, 2020;Mirman et al, 2018aMirman et al, , 2018b. However, a recent survey found only 62% of primary care physicians were comfortable counseling their patients on driving (Gaw et al, 2020).…”
mentioning
confidence: 99%
“…Several studies have reported parents, adolescents, and providers themselves consider the teen's primary care physician a resource for information about transportation topics, and in particular, independent driving (Ford et al, 2016;Gaw et al, 2020;Mirman et al, 2018aMirman et al, , 2018b. However, a recent survey found only 62% of primary care physicians were comfortable counseling their patients on driving (Gaw et al, 2020). Further, autistic individuals may experience unique challenges during provider-patient interactions (e.g., communication and sensory difficulties; Duker et al, 2019).…”
mentioning
confidence: 99%